Utility of 18F-FDG PET/CT in the diagnosis and staging of extramammary Paget's disease. Issue 9 (September 2015) - Tian, Ying; Wu, Hu-Bing; Li, Dong-Li; Li, Hong-Sheng; Zhou, Wen-Lan; Wang, Quan-Shi
<x xml:space="preserve">Abstract</x> Purpose Extramammary Paget's disease (EMPD) is rare, and limited data have been reported on the utilization of fluorine-18 fluorodeoxyglucose PET/computed tomography (18F-FDG PET/CT) in this disease. The aim of this study is to evaluate the role of 18F-FDG PET/CT in the diagnosis and staging of EMPD. Materials and methods Whole-body 18F-FDG PET/CT images of 10 patients with newly diagnosed or recurrent EMPD were retrospectively analyzed. The lesion with increased 18F-FDG uptake was considered positive and was measured using the maximum standardized uptake value (SUVmax). The results of PET/CT were compared by conventional staging examinations. Results All malignant lesions showed increased 18F-FDG uptake, except for some small lung metastases. Whole-body 18F-FDG PET/CT detected all primary lesions in four newly diagnosed patients and recurrences in the primary sites in two patients. Two thick lesions showed intense uptake of 18F-FDG (SUVmax: 14.9 and 7.5) whereas four thin lesions had only mild 18F-FDG uptake (mean SUVmax: 3.25±0.24). A false-positive result was found in one patient with suspected primary recurrence. 18F-FDG PET/CT also detected lymph node metastases in six patients, bone metastases in five patients, liver metastases in two patients, lung metastases in one patient, and an adrenal gland metastasis in one patient. Compared with conventional staging examinations, three of 10 patients were upstaged by PET/CT. Conclusion 18F-FDG PET/CT diagnosis of primary lesions in EMPD is mainly dependent on the thickness of the lesions, whereas it is more sensitive for the diagnosis of metastases.